PERAN GURU BIMBINGAN KONSELING DALAM MEMBENTUK ETIKA PERGAULAN SISWA DENGAN TEMAN SEBAYA DI LINGKUNGAN SEKOLAH [THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN FORMING STUDENTS ETHICS OF ASSOCIATION WITH PEERS IN THE SCHOOL ENVIRONMENT] - Taebenu, Melania Desry; Bone, Matilda Pia (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to analyze the role of Guidance and Counseling (BK) teachers in improving students' time management skills to reduce the habit of being late to school. The phenomenon of student tardiness is still a common problem at various levels of education and is often associated with weak discipline and time management skills. This study used a qualitative approach with a case study design conducted at SMA Negeri 4 Kupang in September-October 2025. Research participants consisted of BK teachers, homeroom teachers, and grade XI students selected through purposive sampling techniques. Data were collected through semi-structured interviews, participant observation, and documentation studies, then analyzed using data reduction, data presentation, and conclusion drawing and verification. The results of the study revealed three main themes: (1) BK teachers as facilitators of student self-awareness in understanding the importance of time management, (2) the application of disciplinary development strategies based on reflective and empathetic counseling, and (3) collaboration between BK teachers, homeroom teachers, and parents in establishing positive student routines. These findings confirm that the role of BK teachers is not only curative, but also preventive and collaborative in building disciplined behavior.